Stabilization of frequency in multi-microgrid system using barnacle mating optimizer-based cascade controllers - Peddakapu, kurukuri; Srinivasarao, P.; Mohd Rusllim, Mohamed; Arya, Yogendra; Krishna Kishore, Dokala Janandra (Elsevier Ltd, 2022)
This paper presents a new control strategy in multi-microgrid system for supressing the variations of frequency and of tie-line power flow due to intermittent nature of renewable sources and frequently varying load demands. A novel cascade combination of fractional order-based integral derivative and proportional integral derivative with filter called CFOID-FOPIDN controller is utilized as secondary controller for automatic generation control. In this work, diverse sources such as photovoltaic, wind, diesel engine, fuel-cell, electrical vehicles and battery energy storage systems are considered for investigations under various uncertainties conditions. A newly developed barnacle mating optimizer is presented to tune the CFOID-FOPIDN for diminishing the frequency and tie-line power changes. Moreover, the amalgamation of redox flow batteries and modern flexible alternating current transmission system device like distributed power flow controller is integrated into the system for ameliorating the dynamic stability of the system. The tested outcomes show that the barnacle mating optimizer-based CFOID-FOPIDN controller with the combination of distributed power flow controller and redox flow batteries exhibits low fluctuation rate for frequency (5.6 s for area-1 and 5.5 s for area 2) and tie-line power (6.2 s). Finally, the robustness of the CFOID-FOPIDN is validated under three operating conditions, such as step load perturbations, change in wind speed, irradiance, and change in both wind and irradiance levels.